Dangerous or in Danger? Exploring Safety, Omission, and Beauty in Rebecca Hall’s Passing (2021) - Sivanesan, Mathuri (Pivot: A Journal of Interdisciplinary Studies and Thought, 2023)
Rebecca Hall’s 2021 adaptation of Nella Larsen’s Passing, establishes themes of safety in a visual context, examining the Black bodily experience in both white and Black spaces. Hall’s use of greyscale lighting, diegetic & non-diegetic sounds, and, most importantly, omission, spotlights what it means to be Black in white space. In the same way Larsen’s story rejects the possibility of ever being safe as a Black person, regardless of whether one can pass as white or not, Hall’s cinematic methodology reveals the character of Clare as both dangerous and yet always in danger. Controlling what the viewer is allowed to see, Hall presents a newfound method of storytelling that confronts Black violence in a manner that rejects the glorification of Black trauma, while also presenting the dangers Black persons face from merely existing in their body.